2017
DOI: 10.1099/jgv.0.000974
|View full text |Cite
|
Sign up to set email alerts
|

Baculoviruses require an intact ODV entry-complex to resist proteolytic degradation of per os infectivity factors by co-occluded proteases from the larval host

Abstract: Baculoviruses orally infect caterpillars in the form of occlusion-derived viruses (ODVs). The ODV-envelope contains a number of proteins which are essential for oral infectivity, called per os infectivity factors (PIFs). Most of these PIFs are involved in the formation of an ODV-entry complex that consists of a stable core, formed by PIF1, PIF2, PIF3 and PIF4, and the more loosely associated PIFs P74 (PIF0) and P95 (PIF8). PIF1, PIF2 and PIF3 are essential for formation of the stable core, whereas deletion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…Consistent with previous reports (3,22,23), the AcMNPV PIF complex contained eight PIFs (PIF0 to -4 and PIF6 to -8) and lacked PIF5 (Fig. 1A).…”
Section: Bn-page Andsupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with previous reports (3,22,23), the AcMNPV PIF complex contained eight PIFs (PIF0 to -4 and PIF6 to -8) and lacked PIF5 (Fig. 1A).…”
Section: Bn-page Andsupporting
confidence: 93%
“…Western blot analysis confirmed that the AcMNPV PIF complex was approximately 500 kDa ( Fig. 1A), as reported previously (3,22,23). By use of anti-AcMNPV PIF antibodies, a similar, ϳ500-kDa complex was detected in the closely related virus BmNPV (Fig.…”
Section: Bn-page Andsupporting
confidence: 89%
See 3 more Smart Citations